The tea rose under glass - Evans, Charles Silar (My University, 1896)
Introduction: The tea rose is the most beautiful of all roses raised for market. It’s refinement of color and its powerful fragrance makes it the center of loveliness. It is a native of China. Botanical name Rosa Indica Odorata. The tea class is much more uniform in the characteristics of the different varieties than any of the other large groups. In judging its merits we lay less stress on fullness of flower than on the beauty of the bud. The flower varies same in size and fullness, but little compared with other varieties.
Citation: Evans, Charles Silar. The tea rose under glass. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Tea rose; China; Flower; Beauty; Theses; Manuscripts (documents)